DEVELOPMENT OF PROBLEM BASED LEARNING ORIENTED HIGH ORDER THINKING SKILLS IN CLASS V ELEMENTARY SCHOOL STUDENTS - Maratul Qiftiyah; Teguh Yunianto; Atika Nur Hidayati; Tri Maya Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The success of developing problem-based learning LKPD teaching materials that are oriented towards High Order Thinking Skills for high-class students and testing the feasibility, convenience and attractiveness of the LKPD teaching materials. The research method used is development research using four stages, namely: the definition stage (define), the design stage (Design), the development stage (Development). The instruments used in this study were questionnaires and documentation. The questionnaire consisted of media experts, material experts, linguists, practitioners (educators) and student response questionnaires. Data analysis techniques using quantitative descriptive. The results of this study show that the feasibility level for material is 89.25%, media is 82.8% and for linguists is 88.4%. So from these three aspects it can be concluded that problem based learning LKPD oriented High Order Thinking Skills in thematic learning is very suitable for use in learning. The teacher's response got a score of 91.18%, seen from the students' response questionnaire, they got an average score of 81.17% and achieved very interesting criteria, which means that problem based learning LKPDs oriented to High Order Thinking Skills in students are very interesting or very proper to use.